Sleep Quality and Faculty Performance: A Multivariate Analysis of Influencing Factors - Ramadhani, Fitria; Ambarsarie, Riry; Anggraini, Rizkianti; Dita, Diah Ayu Aguspa; Febrianti, Syeri (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2025)
Sleep quality is a crucial factor influencing the overall well-being and performance of individuals, including university staff. Several studies have highlighted that sleep quality among university staff can be influenced by various factors, including workload, stress levels, work-life balance, and environmental conditions. This study conducted to analyzing the factors related to sleep quality and their impact on the work performance of staff at Universitas Bengkulu. This analytical observational with a cross-sectional approach was conducted on a sample of 115 teaching staff at Universitas Bengkulu, who met the criteria lecturers at Universitas Bengkulu, aged 25-65, and who have been teaching for at least three months. Sleep quality is measured with the Pittsburgh Sleep Quality Index (PSQI) and individual productivity is assessed using the Individual Work Productivity Questionnaire (IWPQ). The data analysis methods used are Chi-Square, Simple Logistic Regression, and Multiple Logistic Regression. The result of this study there is a significant relationship between sleep quality (p=0.041); sleep duration (p=0.02); and activity disfunction (p=0.029) with work performance. In the final multivariate modeling, logistic regression analysis revealed that the variables significantly related to work performance are sleep duration and activity dysfunction (p=0.001). For conclusion, the study found that poor sleep quality and activity dysfunction significantly impact work performance, with less than 5 hours of sleep increasing the risk of low performance by up to 10.6 times. Despite high sleep efficiency, inadequate sleep duration and daytime activity issues were key factors contributing to reduced productivity